The Impact of Water Quality on Beef Cattle Health and Performance - Megan N. Brew; Jeffrey Carter; Mary K. Maddox (EDIS, 2009)
AN187, a 4-page illustrated fact sheet by Megan N. Brew, Jeffrey Carter, and Mary K. Maddox, discusses common contaminants of drinking water and how to evaluate drinking water management practices. Includes references. Published by the UF Department of Animal Sciences, November 2008.